Manejo integral de la artrosis glenohumeral: tratamiento conservador y quirúrgico - Martinez Zaput, Emily Nicole (Machala : Universidad Técnica de Machala, 2024)
Introduction: Glenohumeral osteoarthritis is a degenerative disease of the shoulder joint that causes pain and limited mobility. This condition can have a significant impact on the patient's quality of life. Development: A comprehensive review of the literature on glenohumeral osteoarthritis reveals a variety of therapeutic approaches ranging from conservative therapies to advanced surgical options. Analysis of the efficacy and results of conservative treatments such as physical therapy, lifestyle modifications, and anti-inflammatory drugs are evident. Although intra-articular injections and biologic therapies have promising results, the lack of evidence does not recommend their use at this time. In addition, we compared surgical treatment options and presented recent techniques that best fit patients' personal characteristics.
Introducción: La artrosis glenohumeral es una enfermedad degenerativa de la articulación del hombro que causa dolor y limitación de la movilidad. Esta condición puede tener un impacto significativo en la calidad de vida del paciente. Desarrollo: Una revisión exhaustica de la literatura sobre la artrosis glenohumeral revelan una variedad de enfoques terapéuticos que van desde las terapias conservadoras hasta las opciones quirúrgicas avanzadas. El análisis de la eficacia y los resultados de tratamientos conservadores como fisioterapia, modificaciones de los estilos de vida, y fármacos antiinflamatorios son evidentes. Aunque las inyecciones intraarticulares y las terapias biológicas tienen resultados prometedores, la falta de evidencia no recomienda su uso hasta el momento. Además, se comparó las opciones de tratamiento quirúrgico y se expone técnicas recientes que mejor se ajusta a características personales de los pacientes.
Keywords: ARTROSIS GLENOHUMERAL; DEGENERACION ARTICULAR; HOMBRO; TRATAMIENTO